Clinical epidemiological characterization of suspected and positive patients to COVID-19 in Puerto Padre - Yoenny Peña García; Bertha Nieves Domínguez Fernández; Katia Gómez Cook; Dunia Garrido González; Ana María Labrada Solorzano (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: The COVID-19 is an emergent disease that has affected everybody in a pandemic way, with high sanitary, economic and social costs.   Objective: To characterize suspected and positive patients to COVID-19 according to selected clinical epidemiological variables.  Methods: An observational, descriptive and cross-sectional study of 565 patients, assisted in the municipality of Puerto Padre, Las Tunas, was carried out from February to May, 2020. The information was obtained from the epidemiological surveys. The following variables were analyzed: incidence, age, sex, health area, case definition, infection source, clinical forms, result of the RT-PCR, symptoms and signs, comorbidities, as well as diagnosis when discharged from the institution.  Results: In the confirmed patients, the most frequent age group was 15 to 29 with 3 cases (42.9 %), followed by those of 30 at 44 with 2 cases (28.6 %) and a mean age of 31 years. The health area with a higher risk of incidence was that of Delicias with a rate of 13.91 every 100 000 inhabitants (3 affected). The cases were: imported and introduced (1 case each for 14.3 %) and autochthonous (5 for 71.4 %). The most frequent signs and symptoms in cases with positive RT-PCR were fever (28.6 %), nasal obstruction, cough and rhinorrhea (14.3 % each). The comorbidities that prevailed were hypertension (28.6 %), nicotine addiction (28.6 %) and bronchial asthma (14.3 %).   Conclusions: COVID-19 affected young people with prevalence in the asymptomatic clinical form.